(untitled) (CIPEEX, 2025)
Trauma is one of the leading causes of mortality and disability among adults and youths, resulting in serious economic and social consequences due to high medical costs and reduced productivity. In traffic accidents, injuries can lead to chronic pain, psychological suffering, and decreased quality of life, compromising work capacity. Therefore, it is crucial to understand the epidemiological profile of these accidents and identify the primary mechanisms of injury that result in disability. Thus, the aim of this study was to evaluate the epidemiological profile of volunteer patients in the postoperative period of lower limb trauma, highlighting the main mechanisms and types of injuries. This cross-sectional and quantitative study involved an epidemiological survey of lower limb traumas in the postoperative period. The research was conducted with volunteers at a referral orthopedics unit in the central-northern region of Goiás, with ethical approval (opinion no. 6970562). The study included volunteers aged 18 to 60, of both sexes, in the postoperative period of lower limb trauma, who consented to participate through the Informed Consent Form (ICF). The study involved 92 patients, of whom 64 (69.6%) had fractures, primarily caused by falls (31.3% of cases) followed by motorcycle accidents (20.3%). Only one case of partial injury was reported, resulting from a fall. Additionally, 27 (29.3%) cases of ligament ruptures were recorded, mostly related to sports injuries. Regarding injury distribution by sex, fractures affected 22 (34.4%) women and 42 (65.5%) men. The only partial injury occurred in a woman. For ligament ruptures, 6 (22.2%) occurred in women and 21 (77.8%) in men. However, statistical analysis using the Chi-Square test did not show a significant association between injury types and sex (p=0.174). The data analysis of this study provides a detailed view of the epidemiological profile of patients in the postoperative period of lower limb trauma, highlighting the most common mechanisms and types of injuries. Partial injuries are rare and associated with falls, while ligament ruptures, primarily related to sports, represent a significant demand for orthopedic care. The prevalence of injuries was higher in men, although without a statistically significant difference. These data emphasize the importance of strategies to prevent falls, accidents, and sports injuries, aiming for better outcomes and reduced orthopedic treatment costs.